Implementation Wisdom Local in History Learning To Appreciation Islamic Based High School/MA Students in Regency Wonosobo - Assidiq, Nissa Fazalina; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2022)
The study aims to describe the cultivation of local wisdom in historical learning, analyzing how the appreciation of Islamic-based high school / MA students in Wonosobo District for learning history, knowing what obstacles historical teachers face in instilling local wisdom in Islamic-based high school / MA students in Wonosobo Regency. The method used is qualitative descriptive. The data source consists of informants, events, and archives/documents—techniques for collecting data through direct observation, in-depth interviews, and document studies. Test the validity using Triangulation—data analysis with data reduction, data presentation, and conclusion. The results showed that in the cultivation of the value of local wisdom in learning history in the three schools, the teacher developed his learning, which was associated with the traditions and results of Hindu-Buddhist culture in the student environment through interactive lecture learning methods, discussions, visits to historical sites and map learning media concepts, PPT and videos about the Dieng temple complex. The appreciation shown by students can interpret and assess the existence of relics and traditions from the Hindu-Buddhist religion. External constraints in planting local wisdom in the three schools are the lack of unique programs from schools to instill local wisdom, limited learning resources, and internal constraints, namely, the lack of experience of students following regional cultural activities and boredom with monotonous learning systems.